Community service as a form of punishment / Hani Iryani Bonny Leong, Fadhilah Md Fazil - Bonny Leong, Hani Iryani; Md Fazil, Fadhilah (2011)
This research is conducted to introduce the concept of community service and the benefits that it brings not just to the community at large but also to individuals who commits themselves in community service. The unique long standing effect characteristics of community service are also shared in this research. Recommendation to inject the concept of community service as an alternatives method of punishment for the petty crimes in UiTM specifically in combating the misdemeanour of wrongful car park in the UiTM is also put forward. The potential benefits and its rate of success is also provided in this research.This is a library based research including primary and secondary sources including interviews. This research is very realistic and idealistic for the purpose of improving the current system of punishment in UiTM that is regarded as flawed and unreliable.